Financial and trade openness: Evidence on emerging market regional groups - (:unkn) unknown (My University, 2011)
The aim of this paper is to investigate the impact of trade and interest rate differential on the financial openness of Central and Eastern European, Latin American and East Asian countries. Second generation panel analyses display a long run relationship between financial openness, trade openness and interest rate differentials in all three regions. Panel Granger causality tests reveal unidirectional causality both from trade openness and (interest rate differentials) to FDI and portfolio investments again in all three regions. FMOLS results disclose that the impact of trade openness and (interest rate differentials) varies according to the emerging country group. © EuroJournals, Inc. 2011.
Keywords: Financial openness; Interest Rates; Second Generation Panel Analyses; Trade openness